Enhanced Self-Control for the Prevention of Pornography of Student in Senior High School - Ahsanul Hafizh; Firman Firman; Netrawati Netrawati (Universitas Negeri Padang, 2021)
The lack of students' self-control led to the emergence of pornography. The phenomenon of pornography is a general term that refers to sexually explicit material that may be softcore or hardcore and can also be referred to as things that attempt to stimulate and increase sex drive with text and images. Self-control is the ability to organize, guide, regulate, and direct forms of behavior that can lead to positive consequences. The purpose of this study was to describe students' self-control at SMA N 1 Merbau. This research uses descriptive analysis. The research sample consisted of 128 students who were taken using purposive sampling technique. The instrument used was